2019
DOI: 10.1155/2019/4861081
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Four Polymorphisms in Renin-Angiotensin-Aldosterone-Related Genes to Hypertension in a Thai Population

Abstract: Introduction. The roles of genes in the renin-angiotensin-aldosterone system (RAAS) in hypertension, including angiotensin-converting enzyme (ACE), angiotensinogen (AGT), angiotensin II receptor type 1 (AGTR1), and aldosterone synthase (CYP11B2), have been widely studied across different ethnicities, but there has been no such investigation in Thai population. Materials and Methods. Using 4,150 Thais recorded in the Electricity Generating Authority of Thailand (EGAT) study, we examined the association of rs179… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Essential arterial hypertension (EAH) affects about 25–43% of the population worldwide. Medical experts estimate that EAH is the most common disease globally: from 1 billion people in 2000 to 1,6 billion in 2025 [ 1 3 ]. Also, EAH is one of the most important cardiovascular and metabolic risk factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Essential arterial hypertension (EAH) affects about 25–43% of the population worldwide. Medical experts estimate that EAH is the most common disease globally: from 1 billion people in 2000 to 1,6 billion in 2025 [ 1 3 ]. Also, EAH is one of the most important cardiovascular and metabolic risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Wang L. et al [ 17 ] found that VDR polymorphisms BsmI and FokI are linked to hypertension in the US population. Even though genetic predictors of RAAS activity, including EAH, have been studied widely throughout the last decade [ 1 , 10 , 18 22 ], a number of them remain unexplored, especially in the Ukrainian population.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is a multifactorial disease with the interaction of many risk factors, and environmental and strong genetic backgrounds (3). The most studied genetic factors are those involved in the renin-angiotensin-aldosterone system activity (RAAS), such as angiotensinogen gene (AGT), angiotensin-converting enzyme (ACE), angiotensin II receptor gene (AGTRII), as well as modifi ed factors such as obesity, increased body mass index (BMI), excessive salt intake, alcohol consumption, stress, low levels of high density lipids (HDL) and total cholesterol increase (4)(5)(6)(7)(8)(9). Genes determine approximately 20-60 % of blood pressure (BP) variability and some peculiarities of hypertension-mediated organ damage in different populations (10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 12 Nevertheless, one report suggested that rs1799998 is not associated with hypertension or other cardiovascular indicators in a population in Thailand. 13 …”
Section: Introductionmentioning
confidence: 99%
“…8,12 Nevertheless, one report suggested that rs1799998 is not associated with hypertension or other cardiovascular indicators in a population in Thailand. 13 Recent population-based studies established the association of the À344C/T CYP11B2 polymorphism with the risk of cardiovascular diseases. 14,15 Because of differences in À344C/T allele frequencies and incidences of cardiovascular disorders in different ethnicities, these results may not be applicable to the Chinese population.…”
Section: Introductionmentioning
confidence: 99%